1997
DOI: 10.1212/wnl.49.3.878
|View full text |Cite
|
Sign up to set email alerts
|

A 44-month clinical-brain MRI follow-up in a patient with B 12 deficiency

Abstract: We report a 51-year-old woman with vitamin B12 deficiency who presented with slight megaloblastic anemia and severe neurologic deficits associated with multiple focal and confluent T2-weighted white matter hyperintensities on brain MRI. Forty-four months after initiation of hydroxocobalamin therapy, there was clinical improvement and striking reduction in the MRI abnormalities. B12 deficiency should be considered in the differential diagnosis of neurologic disorders associated with multiple areas of white matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 3 publications
2
19
0
1
Order By: Relevance
“…Areas of demyelination on brain MRI have been described in vitamin B12-deficient patients or in those with diseases that affect vitamin B12 metabolism. [33][34][35] Thus, our findings lend support for the contention that poor vitamin B12 status is a risk factor for brain atrophy and possibly WMHV which in turn may contribute to cognitive impairment. The single MRI measure in the present study prevents direct investigation of whether poor vitamin B12 status results in cognitive decline by promoting faster rates of total brain atrophy or demyelination in selected white matter areas.…”
Section: Resultssupporting
confidence: 77%
“…Areas of demyelination on brain MRI have been described in vitamin B12-deficient patients or in those with diseases that affect vitamin B12 metabolism. [33][34][35] Thus, our findings lend support for the contention that poor vitamin B12 status is a risk factor for brain atrophy and possibly WMHV which in turn may contribute to cognitive impairment. The single MRI measure in the present study prevents direct investigation of whether poor vitamin B12 status results in cognitive decline by promoting faster rates of total brain atrophy or demyelination in selected white matter areas.…”
Section: Resultssupporting
confidence: 77%
“…Cobalamin levels below 100 pg/ml represent significant tissue deficiency of B 12 , and levels between 100 and 300 pg/ml justify testing for the metabolites homocysteine and methylmalonic acid, elevations of which also signify clinically relevant B 12 deficiency (Miller et al 2005). Well documented cases of dementia with MRI white matter lesions have demonstrated that treatment using parenteral vitamin B 12 improve both the dementia and the white matter changes (Chatterjee et al 1996;Stojsavljević et al 1997).…”
Section: Metabolic Disordersmentioning
confidence: 99%
“…223,224 A high prevalence of WMHs is also found in 22q11-deletion syndrome frequently associated with psychosis, 225 cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, which is caused by mutations in the NOTCH3 gene on chromosome 19 and frequently associated with depression, and other less common genetic conditions. [226][227][228][229] Nongenetic factors are associated with WMHs as well; [230][231][232][233][234][235][236][237][238] for example, Moore et al 239 reported a correlation between WMH and season of birth in a group of patients with BD. Thus, it appears that WMHs are not specific to BD and their usefulness as an endophenotype remains to be established.…”
Section: Basal Gangliamentioning
confidence: 99%